Tailor-made legumain/pH dual-responsive doxorubicin prodrug-embedded nanoparticles for efficient anticancer drug delivery and in situ monitoring of drug release. Issue 4 (16th January 2020) - Li, Yang; Niu, Yimin; Zhu, Jianhua; Gao, Cuicui; Xu, Qunwei; He, Zhiyu; Chen, Dawei; Xu, Ming; Liu, Yang
Abstract : Legumain enzyme is a well-conserved lysosomal cysteine protease that is overexpressed in many tumor cells and tumor stromal cells. Herein, we developed a legumain/pH double-sensitive nanosystem for targeted tumor therapy. Abstract : Legumain enzyme is a well-conserved lysosomal cysteine protease and is over-expressed in many tumor cells and tumor stromal cells and exhibits higher protease activity under acidic conditions, such as in lysosomes and endosomes. Legumain enzyme-triggered drug delivery systems have demonstrated potential therapeutic values in cancer targeted therapy. To realize a more efficient delivery of anticancer therapeutic agents, we herein report a legumain/pH dual-responsive drug delivery system for enhancing site-specific controlled release of antitumor drugs. The carrier (named "DS-NA") is a hybrid vector constituting PEG- b -PBLA polymers, pH-responsive OAPI polymers, and legumain-sensitive peptide-doxorubicin prodrug decorated fluorescent carbon dots (CDs-C9-AANL-DOX). In tumor cells, DS-NA could disassemble rapidly in acidic environments, and then release doxorubicin through legumain digestion. Except as a drug vector, the drug release process from DS-NA could also be dynamically monitored by CLSM as the DOX was released from the surface of CDs through the AANL peptide linker digested by legumain, then transferred into the cell nucleus and exerted cytotoxicity, while the CDs themselves remained in the cytoplasm. As a control, the CDs-C9-DOX, which did not contain the AANL peptide linker, also still resided in the cytoplasm. Furthermore, in vivo studies show that DS-NA had a stronger inhibitory effect on tumor tissue with attenuated side effects to normal tissues than control nanoparticles or free drugs, which may be due to comprehensive effects including pH/legumain dual-triggered drug release, long blood circulation periods, and EPR effects. Together, a combination strategy of acid sensitivity and legumain enzyme sensitivity used for site-specific controlled release of drugs provides a novel method for enhanced and precise antitumor chemotherapy.